Functional Roles of the Nuclear Localization Signal of Parathyroid Hormone-Related Protein (PTHrP) in Osteoblastic Cells - García-Martín, A. (Mol Endocrinol, 2014)
PTHrP is an important regulator of bone remodelling, apparently by acting through several sequence domains. We here aimed to further delineate the functional roles of the nuclear localization signal (NLS) comprising the 88–107 amino acid sequence of PTHrP in osteoblasts. PTHrP mutants from a human PTHrP (−36/+139) cDNA (wild type) cloned into pcDNA3.1 plasmid with deletion (Δ) of the signal peptide (SP), NLS, T(107), or T107A replacing T(107) by A(107) were generated and stably transfected into osteoblastic MC3T3-E1 cells. In these cells, intracellular trafficking, cell proliferation and viability, as well as cell differentiation were evaluated. In these transfected cells, PTHrP was detected in the cytoplasm and also in the nucleus, except in the NLS mutant. Meanwhile, the PTH type 1 receptor (PTH1R) accumulates in the cytoplasm except for the ΔSP mutant in which the receptor remains at the cell membrane. PTHrP-wild type cells showed enhanced growth and viability, as well as an increased matrix mineralization, alkaline phosphatase activity, and osteocalcin gene expression; and these features were inhibited or abolished in ΔNLS or ΔT(107) mutants. Of note, these effects of PTHrP overexpression on cell growth and function were similarly decreased in the ΔSP mutant after PTH1R small interfering RNA transfection or by a PTH1R antagonist. The present in vitro findings suggest a mixed model for PTHrP actions on osteoblastic growth and function whereby this protein needs to be secreted and internalized via the PTH1R (autocrine/paracrine pathway) before NLS-dependent shuttling to the nucleus (intracrine pathway).